PENGAMBILAN KEPUTUSAN PENENTUAN GURU BERPRESTASI PADA MA AL MAHFUZHIYAH MENGGUNAKAN METODE TOPSIS - Sumarlin, Fitrahayu; Muslihudin, Muhamad (JMPA (Jurnal Manajemen Pendidikan Al-Multazam), 2019)
Computer-based information system (Computer Based Decision Support System) is currently developing very rapidly along with the progress of the development of people's lives, one of which relates to the provision of relevant systems in decision making. MA Al Mahfuzhiyah is one of the madrassas in Central Lampung District that tries to improve the quality of education by prioritizing the quality of educators and education personnel. Provide added value and enthusiasm the MA Al Mahfuzhiyah teachers give awards to outstanding teachers. In the selection of high achieving teachers, assessment needs to be done so that the objectives give satisfaction to those who will be given an award. Selection of topical methods as a media for evaluating teacher performance to determine teacher achievement Based on the results of these calculations, then a large sample taken in this study determined 3 people. From the results of topsis test with 3 samples obtained V3 or the sample of having the highest value then V1 with sequence number two and V2 has the lowest value and placed number three.